Metadiscourse use in the persuasive writing of Malaysian undergraduate students - Tan, Helen; Wong, Bee Eng (Canadian Center of Science and Education, 2014)
Metadiscourse is a prevalent linguistic resource that helps writers to manage the flow of the propositional contents and to direct their stance towards their contents and readers. Its dominance in persuasive writings has motivated this study which is to examine the occurrences and forms of metadiscourse use in the writing of both the high (HEP) and low (LEP) English proficiency Malaysian undergraduate writers. Both the quantitative and qualitative findings of the metadiscourse use were obtained using a concordance software (MP2.2). The results indicated that between the two main domains of metadiscourse, both groups of writers exhibited a greater preference for the use of interactional metadiscourse than the interactive. Between the two groups of writers, it was the HEP writers who exhibited a higher frequency of use for both the interactive and interactional metadiscourse. In terms of the forms used, the HEP writers also used a greater variety of metadiscourse forms when compared to the LEP writers. Based on the results, it can be concluded that the HEP writers had a greater awareness of the academic writing conventions, while the LEP writers still lacked this awareness in their writing. Furthermore, variant forms of metadiscourse use were also noted. This finding implies that more instructional help may be needed to raise the LEP writers’ awareness on the importance of metadiscourse use in a persuasive discourse.